Time‐Dependent ATR‐FTIR Spectroscopic Studies on Fatty Acid Diffusion and the Formation of Metal Soaps in Oil Paint Model Systems - Baij, Lambert; Hermans, Joen J.; Keune, Katrien; Iedema, Piet (Angewandte Chemie International Edition, 2018)
The formation of metal soaps (metal complexes of saturated fatty acids) is a serious problem affecting the appearance and structural integrity of many oil paintings. Tailored model systems for aged oil paint and time‐dependent attenuated total reflection Fourier transform infrared (ATR‐FTIR) spectroscopy were used to study the diffusion of palmitic acid and subsequent metal soap crystallization. The simultaneous presence of free saturated fatty acids and polymer‐bound metal carboxylates leads to rapid metal soap crystallization, following a complex mechanism that involves both acid and metal diffusion. Solvent flow, water, and pigments all enhance metal soap crystallization in the model systems. These results contribute to the development of paint cleaning strategies, a better understanding of oil paint degradation, and highlight the potential of time‐dependent ATR‐FTIR spectroscopy for studying dynamic processes in polymer films. The formation of metal soaps (metal complexes of saturated fatty acids) is a serious problem affecting the appearance and structural integrity of many oil paintings. Tailored model systems for aged oil paint and time‐dependent ATR‐FTIR spectroscopy were used to study the diffusion of palmitic acid and subsequent metal soap crystallization.